Mammalian gastrointestinal tract parameters modulating the integrity, surface properties, and absorption of food‐relevant nanomaterials. (30th January 2015) - Bellmann, Susann; Carlander, David; Fasano, Alessio; Momcilovic, Dragan; Scimeca, Joseph A.; Waldman, W. James; Gombau, Lourdes; Tsytsikova, Lyubov; Canady, Richard; Pereira, Dora I. A.; Lefebvre, David E.
<x xml:space="preserve">Abstract</x> Many natural chemicals in food are in the nanometer size range, and the selective uptake of nutrients with nanoscale dimensions by the gastrointestinal (GI) tract is a normal physiological process. Novel engineered nanomaterials (NMs) can bring various benefits to food, e.g., enhancing nutrition. Assessing potential risks requires an understanding of the stability of these entities in the GI lumen, and an understanding of whether or not they can be absorbed and thus become systemically available. Data are emerging on the mammalian in vivo absorption of engineered NMs composed of chemicals with a range of properties, including metal, mineral, biochemical macromolecules, and lipid‐based entities. In vitro and in silico fluid incubation data has also provided some evidence of changes in particle stability, aggregation, and surface properties following interaction with luminal factors present in the GI tract. The variables include physical forces, osmotic concentration, pH, digestive enzymes, other food, and endogenous biochemicals, and commensal microbes. Further research is required to fill remaining data gaps on the effects of these parameters on NM integrity, physicochemical properties, and GI absorption. Knowledge of the most influential luminal parameters will be essential when developing models of the GI tract to quantify the percent absorption of food‐relevant engineered NMs for risk assessment. WIREs Nanomed Nanobiotechnol 2015, 7:609–622. doi: 10.1002/wnan.1333 For further resources related to this article, please visit the WIREs website.